2010
DOI: 10.1111/j.1365-2222.2010.03599.x
|View full text |Cite
|
Sign up to set email alerts
|

Environmental epigenetics and allergic diseases: recent advances

Abstract: Significant strides in the understanding of the role of epigenetic regulation in asthma and allergy using both epidemiological approaches as well as experimental ones have been made. This review focuses on new research within the last two years. These include advances in determining how environmental agents implicated in airway disease can induce epigenetic changes, how epigenetic regulation can influence T helper cell (Th) differentiation and T regulatory (Treg) cell production, and new discoveries of epigene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 81 publications
0
31
0
Order By: Relevance
“…A more complete understanding of the control of developmental processes that occur during early-life maturation of the T-cell compartment may yield insights relevant to a range of autoimmune and allergic disorders. 26,27 Integration of DNA methylation and gene expression data on a genome-wide scale revealed that a direct relationship between DNA methylation and gene expression is often difficult to infer. Indeed, only a subset of probes on the methylation array Epigenetic programming of CD4 þ T-cell phenotypes during early life D Martino et al correlated with gene expression measurements in the expected direction based on the current dogma of DNA methylation being largely inhibitory to gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…A more complete understanding of the control of developmental processes that occur during early-life maturation of the T-cell compartment may yield insights relevant to a range of autoimmune and allergic disorders. 26,27 Integration of DNA methylation and gene expression data on a genome-wide scale revealed that a direct relationship between DNA methylation and gene expression is often difficult to infer. Indeed, only a subset of probes on the methylation array Epigenetic programming of CD4 þ T-cell phenotypes during early life D Martino et al correlated with gene expression measurements in the expected direction based on the current dogma of DNA methylation being largely inhibitory to gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to diesel exhaust particles, cigarette smoke and ozone has been reported to cause epigenetic changes in the respiratory tract, which have been implicated in the development of inflammatory lung diseases (Rajendrasozhan et al, 2008; Baccarelli et al, 2009; Ho et al, 2012). DNA methylation and histone modifications are thought to be the major epigenetic mechanisms leading to transcriptional silencing of genes relevant to the development of airway inflammatory and allergic diseases following environmental exposures (Adcock et al, 2007; Kuriakose and Miller, 2010; Ho et al, 2012; Lepeule et al, 2012; Tzouvelekis and Kaminski, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…It is possible that the increase in the prevalence of allergic diseases, including AR, is associated with complex gene-environment interactions. Previous studies have shown that environmental factors contribute to the growing epidemic of allergies worldwide, which are accompanied by epigenetic changes in some cases [3]. …”
Section: Introductionmentioning
confidence: 99%